THE EFFECT OF LIQUIDITY, SOLVABILITY, FIRM GROWTH, AND FIRM SIZE ON PROFITABILITY - Wijayanty, Alexandra Dewi; Susanto, Liana (Graduate Program of Universitas Tarumanagara, 2023)
This research is designed to determine the factors that affect profitability in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. As many as 33 manufacturing companies have been selected using the purposive sample method in this study. The research data were processed using multiple linear regression analysis techniques with EViews 12 software. The result of this research indicate that profitability is not significantly affected by liquidity and firm size. Profitability is negatively affected by solvability. Firm growth has positive effect on profitability.